The Effect Of Profit In Predicting Future Cash Flows (Study Of Plantation And Food Crop Companies On The Indonesia Stock Exchange) - Fitriyani Syukri; Febrina Sari (Journal AK-99, 2023)
The purpose of this study was to determine the effect gross profit, and net profit on future cash flows Both individually and jointly The type of data used is secondary data The data used is the financial statements of plantation and food crop companies listed on the Indonesian stock exchange in 2018 -2020. The analytical technique used in this study is multiple linear analysis, namely regression analysis with two or more independent variables. The result of this study is that gross profit has a positive effect on future cash flows. This is because gross profit is obtained from total sales minus the cost of goods sold. Revenue is obtained in cash or credit, where sales on credit generate future cash inflows. If gross profit increases, cash flow will also increase. Net income has a negative or no significant effect on future cash flows. Because the net income takes into account the magnitude of the tax value. Where the tax value sometimes changes according to government regulations, so that net income is difficult to be used as a predictor in predicting future cash flows. However, both simultaneously affect the prediction of future cash flows. So that investors or interested users really need the company's income statement in making decisions.